Diffusion in the Iron Group L12 and B2 Intermetallic Compounds - Pelleg, Joshua; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book explores diffusion in L12 and B2 structures of Ni3Al, Ni3Ge, Ni3Ga and NiAl, NiGe and NiGa and discusses Fe- and Co-based alloys in detail. These alloys of the VIIIA group elements are the basis of intermetallic compounds known as "super alloys," which are important in many technological high-temperature structural applications to improve mechanical strength properties such as creep. Knowledge of diffusion behavior of intermetallic solids is critical, in particular in high temperature applications of material. Development of high temperature alloys depends on the understanding of diffusion in the aforementioned compounds. Therefore, this comprehensive book on diffusion in the iron group (VIIIA) based intermetallic compounds will be of interest to students, lecturers and researchers. For engineers working in the aircraft industry, this book will prove invaluable as it contains fundamental up to date information and basic knowledge on materials of their interest.
Part A -- 1 Diffusion Equations and Mechanisms -- Part B -- 2 Diffusion Mechanisms in L12 Structures -- 3. Diffusion in Ni3Al -- 4 Diffusion in Ni3Ga -- 5 Diffusion in Ni3Ge -- 6 Diffusion in Fe3Al -- 7 Diffusion Mechanisms in B2 Structures -- 8. Diffusion in NiAl -- 9 Diffusion in NiGa -- 10 Diffusion in CoAl -- 11 Diffusion in CoGa -- 12 Diffusion in FeAl -- Index.
Keywords: Metals; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Metals and Alloys; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics